+0  
 
0
58
6
avatar

i want to help me if it posible

Guest Nov 5, 2017
Sort: 

6+0 Answers

 #1
avatar+338 
0

Is it possible to translate into Enlgish?

supermanaccz  Nov 5, 2017
 #2
avatar+91053 
+2

7.1

It is important to note that both the numerator and the denominator tend to 0 so I will use L'Hopital's rule.

 

 

\(\displaystyle\lim_{x\rightarrow 2}\;\frac{x^2-x-2}{x^2-3x+2}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{\frac{d}{dx}(x^2-x-2)}{\frac{d}{dx}(x^2-3x+2)}\qquad \text{Using L'hopital's Rule }\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{2x-1}{2x-3}\\ =\frac{3}{1}\\ =3\)

Melody  Nov 6, 2017
 #3
avatar+91053 
+2

Это лучший способ сделать это.

This is a better way to do it.

 

\(\displaystyle\lim_{x\rightarrow 2}\;\frac{x^2-x-2}{x^2-3x+2}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{(x-2)(x+1)}{(x-2)(x-1)}\\ =\displaystyle\lim_{x\rightarrow 2}\;\frac{(x+1)}{(x-1)}\\ =\frac{3}{1}\\ =3\)

 

Melody  Nov 6, 2017
edited by Melody  Nov 6, 2017
 #4
avatar+78762 
+2

5.1( a )   arcsin [ cos (pi/3) ] - sin [ arcsin (-1/2) ]  =

               arcsin [ 1/2]  -   (-1/2)

                  pi / 6  +  1/2

      

      (b)  arctan [cos (pi) ] -  arctan [ tan (3pi/ 7) ]  =

             arctan [ -1]    -     3pi/ 7

                - pi/ 4    -   3pi / 7

                 - [ 7 pi  + 12 pi ]  /28

                   - 19pi  / 28

 

5.2 ( a)  arccos [ cos (pi/5) ] - sin [ arctan (-1) ]  =

                   pi  / 5    -    sin [ - pi / 4 ]

                   pi  / 5   -   [ - 1 / √2] 

                   pi  / 5   +  [ 1 / √2]

                   

 

      (b )  arctan [ cos (pi/3) ] -  tan [ arctan (3pi / 7) ] =

              arctan [ 1/2 ]  -  3pi / 7 

 

5.3   (a)  arccos [ cos (pi / 5) ] - sin [ arctan (-1) ]  =

                pi  / 5    -  sin  [ - pi / 4 ] =

                pi  / 5  -  [ - 1 / √2 ]  =

                pi / 5   +  [1 / √2 ]

 

          (b) same as  5.2 (b)

 

 

cool cool cool

CPhill  Nov 6, 2017
 #5
avatar+78762 
+2

lim           √ [2 - x ] - 1

x →1        _________

                     x  - 1

 

 

lim           √ [2 - x ] - 1        √ [2 - x ] + 1 

x →1        _________        __________

                     x  - 1              √ [2 - x ] + 1 

 

lim                2  - x  - 1

x → 1          __________________

                   ( x - 1) (   √ [2 - x ] + 1)

 

lim

x → 1          1 - x

                   ___________________

                   ( x  - 1)  (   √ [2 - x ] + 1)

 

 

lim             - ( x  - 1 )

x → 1       ______________________

                    ( x - 1)  (   √ [2 - x ] + 1)

 

lim                 -1                                                     -1

x → 1          _________________      =              ____     

                     √ [2 - x ] + 1                                       2

 

https://www.desmos.com/calculator/ev6xzdsszs

 

 

cool cool cool

CPhill  Nov 6, 2017
 #6
avatar+78762 
+2

lim                sin (x)

x → pi          _____

                     x -  pi

 

Note   sin (pi- x)  =  sin pi cosx  - sinx cospi  =   sin (x)   .....so........

 

lim            sin ( pi - x)         

x → pi      ________     

                      x - pi           

 

 

 

 1           lim               sin ( pi - x)

__  *     x → pi        __________

-1                                ( pi - x )

 

 

 

 

Note       lim        sin (pi - x)                      lim          sin (x)

             x→ pi     _______       =           x → 0        _____        =    1

                               pi - x                                            x

 

So

 

 

lim                sin (x)

x → pi          _____        =   (-1) * (1)    =   -1

                     x -  pi

 

 

 

cool cool cool

CPhill  Nov 6, 2017

10 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details